The grand chorus of complaint authors and the business ethics of American publishing - Everton, Michael J. (New York ; Oxford : Oxford University Press, 2011)
An engaging study of authorship, ethics, and book publishing in 18th- and 19th-century America, The Grand Chorus of Complaint considers the uneasy relationship between art and commerce with readings of correspondence, newspaper articles, and works by Thomas Paine, Herman Melville, and Fanny Fern.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Publishers and publishing -- Moral and ethical aspects -- United States -- History; Authors and publishers -- United States -- History -- 19th century; Authors and publishers -- United States -- History -- 18th century; Book industries and trade -- United States -- History -- 19th century; Book industries and trade -- United States -- History -- 18th century; Copyright -- United States -- History -- 19th century; Business ethics -- United States -- History